Revisiting Enduring Questions in a Changing Educational Context: A Review of the Handbook of Research on Teacher Education - Mestawot Beyene TAFESE; Erika KOPP (Revista de Știinţe Educaţiei)
The Handbook of Research on Teacher Education: Enduring Questions in Changing Contexts (Third Edition), edited by Marilyn Cochran-Smith, Sharon Feiman-Nemser, D. John McIntyre, and Kelly E. Demers, offers a comprehensive and critical exploration of foundational issues in teacher education. Structured around nine enduring questions, the volume examines the purposes, content, institutional contexts, recruitment and retention, diversity, professional learning, governance, research, and outcomes of teacher education. This edition departs from traditional handbook formats by organizing content through thematic sections, each combining framing essays, historical and contemporary artifacts, and diverse commentaries. The collection draws on multiple philosophical, historical, empirical, and critical perspectives to interrogate longstanding challenges in teacher education. It addresses contemporary concerns such as preparing culturally responsive teachers, supporting democratic and equitable schooling, and advancing teacher identity formation. While the handbook synthesizes a range of scholarly perspectives and includes discussions of research genres (quantitative, qualitative, and critical), it is primarily analytical and conceptual rather than empirical. It does not present original data or formal meta-analyses, and its focus is largely centered on the U.S. context, with limited engagement in international comparative analysis. Similarly, while it critiques standardized evaluation systems and explores the political dimensions of teacher education policy, it stops short of offering a unified framework for assessing program effectiveness. The volume"s emphasis lies in its theoretical richness, historical grounding, and inclusive dialogue among educators, scholars, and policymakers. Future research could build on these foundations by incorporating developments in digital pedagogy, interdisciplinary approaches, and cross-national comparisons. Positioned within broader educational research and policy discourses, the handbook remains a vital resource for scholars and practitioners committed to equity, inclusion, and the continuous reimagining of teacher education in a changing world.